1994
DOI: 10.1017/s0954579400005964
|View full text |Cite
|
Sign up to set email alerts
|

Problems defining resiliency: Illustrations from the study of maltreated children

Abstract: In this article, operational definitions of resiliency used in previous studies are reviewed. Data from a sample of 56 maltreated school-age children are then explored to highlight how variations in the source, type, and number of assessments obtained affect the rates of children classified as resilient. Assessments were obtained in three domains: academic achievement, social competence, and clinical symptomatology. Two sources of information were used to assess each domain, and three different data integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 33 publications
4
52
0
5
Order By: Relevance
“…Moreover, resilience in one domain did not ensure resilience across other domains; at any given wave just over 1 in 10 children lacked clinically significant mental health problems, had average or above-average achievement test scores, and were at least moderately socially competent. The present findings replicate and extend those of a smaller study by Kaufman et al (1994) who found that relatively few maltreated children were consistently competent across domains. Nevertheless, the vast majority of NSCAW children were resilient in at least one domain at each wave (Table 4), which suggests that even though many children were not able to maintain consistently competent functioning in a given domain over time, they did at least manifest competence in one domain or another at each time point.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, resilience in one domain did not ensure resilience across other domains; at any given wave just over 1 in 10 children lacked clinically significant mental health problems, had average or above-average achievement test scores, and were at least moderately socially competent. The present findings replicate and extend those of a smaller study by Kaufman et al (1994) who found that relatively few maltreated children were consistently competent across domains. Nevertheless, the vast majority of NSCAW children were resilient in at least one domain at each wave (Table 4), which suggests that even though many children were not able to maintain consistently competent functioning in a given domain over time, they did at least manifest competence in one domain or another at each time point.…”
supporting
confidence: 89%
“…In practice, however, researchers who study resilience to maltreatment often define resilient children in terms of one criterion: the absence of clinically significant mental health problems. Although this is an important marker of positive functioning, children who lack significant mental health problems may be struggling in other arenas (Kaufman et al, 1994). Moreover, with few exceptions (Cicchetti and Rogosch, 1997;Farber and Egeland, 1987;Herrenkohl et al, 1994), most studies of maltreated children measure children's functioning at a single point in time.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…mental health protection, promotion and recovery) in one multi-level interacting system and (ii) merging theoretical models with an operational (resilience measurement) approach. So far, these theoretical and practical issues have been very poorly linked together and resilience has mainly been measured according to specific operational definitions depending on the aims of individual studies or according to predefined indicators relating to the theoretical position of an inventory's author (Kaufman, Cook, Arny, Jones, & Pittinsky 1994;Vaishnavi, Connor, & Davidson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This real definitional difference can affect the populations that resilience research targets, the methodologies and designs they use, and how research findings are viewed and interpreted. (Cowen, 1997;Kaufman et al, 1994).…”
mentioning
confidence: 99%